ISSUES OF PROTECTION OF LANDLORD’S CIVIL RIGHTS IN THE PRIVATE TENANCY LEGAL RELATIONSHIP - Тімуш, Ірина Сергіївна; Логоша, Віталій Віталійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Objective: the article examines the legal position of the tenant under a tenancy agreement (lease), and also establishes the main problems of the tenant while exercising his civil rights. Research methods: methods of analysis, comparison and synthesis were used. Results: a number of measures are proposed to improve and clarify certain legal norms, in particular, amendments to point 3, paragraph 1, article 825 of the Civil Code, which regulates the right of the tenant to withdraw from the tenant agreement, if the housing became unfit for permanent residence. Discussion: the debating issue is establishing exact time for the termination of mutual rights and obligations between the subjects of the tenant legal relationship in case of exercising an exclusive right unilaterally and at any time to cancel this contract by the tenant. Main material: the Ukrainian legal framework provides the following list of protective measures of subjective civil rights of the tenant under a private tenant contract: unilateral withdrawal of the tenant from the contract at any time of its operation; the right of the tenant to early terminate the contract of hiring an apartment if the housing became unfit for permanent residence in it; the possibility of establishing a longer period for the payment of housing than six months in the tenant contract. Conclusions: civil law provided a sufficiently wide range of measures and methods to protect subjective civil rights of the tenant under a private tenant contract. Also during the study, minor issues with the base of terms and interpretation of certain legal norms were revealed.